SELF REGULATION LEARNING PADA MAHASISWA FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI JAKARTA - Deasyanti Deasyanti; Anna Armeini Rangkuti (Perspektif Ilmu Pendidikan, 2007)
University students have to learn independently. They must have skills of how to learn: thinking ability, thinking process, and learning motivation. Those abilities in cognitive psychology are known as self-regulated learning. This research involve 128 students of Education Faculty of Jakarta State University to know about description of self-regulated learning, difference of self-regulated learning between study programs, and correlation of self-regulated learning withacademic achievement.